Development of a joint mental-health and drug health assessment unit and short-stay unit. (August 2019) - Kealy-Bateman, Warren; McDonald, Andrew; Haber, Paul S; Green, Tim; White, Bethany; Sundakov, Viktoria; O'Cionnaith, Cathal; Glozier, Nicholas
Objectives: There is emerging interest in models of care that focus on assessment and brief inpatient treatment (two to three days) including psychiatric emergency care centre units and short-stay units in Australia. We present the development of a functionally integrated Missenden Assessment Unit and six-bed short-stay unit in the new Professor Marie Bashir Centre at Royal Prince Alfred Hospital in inner-city Sydney. The focus was on collaboration between emergency, drug and alcohol and mental-health services in developing the short-stay unit and Missenden Assessment Unit with joint admission and resource use. We outline the models of care and findings from the 2016 evaluation following the initial two years of operation and consider ongoing challenges. Conclusion: The Missenden Assessment Unit provides an alternative point of presentation for mental-health drug and alcohol patients. The short-stay unit provides coordinated, therapeutic interventions. The Missenden Assessment Unit/short-stay unit reduced the burden of presentations to the emergency department while providing the opportunity for training and collaboration. Further refinement of the models of care should occur with policy development and via research.